DEVELOPMENT OF SPECTROPHOTOMETRICAL ASSAY FOR THE STUDY OF THE INTERACTION OF ANTIOXIDANT STANDARDS WITH 1,1-DIPHENYL-2-PICRYLHYDRAZYL FREE RADICALS - TOUHAMI LANEZ; HADIA HEMMAMI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of the present study was to develop a spectrophotometric based assay for the determination of binding parameters like binding constant and binding free energy of the free and 1,1-diphenyl-2-picrylhydrazyl (DPPH) bound forms of a set of antioxidant standards (AS). The determination of binding constant and binding free energy is based upon the decrease in absorbance of the electronic absorption spectrum of a 10-4 M acetonitrile solution of DPPH in the presence of a given concentration of a solution of antioxidant standards in the same solvent.